2021
DOI: 10.3390/biom11050742
|View full text |Cite
|
Sign up to set email alerts
|

L-Proline Activates Mammalian Target of Rapamycin Complex 1 and Modulates Redox Environment in Porcine Trophectoderm Cells

Abstract: L-proline (proline) is a key regulator of embryogenesis, placental development, and fetal growth. However, the underlying mechanisms that support the beneficial effects of proline are largely unknown. This study used porcine trophectoderm cell line 2 (pTr2) to investigate the underlying mechanisms of proline in cell proliferation and redox homeostasis. Cells were cultured in the presence of 0, 0.25, 0.50, or 1.0 mmol/L proline for an indicated time. The results showed that 0.5 and 1.0 mmol/L proline enhanced c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…As expected, specific signaling modulators such as halofuginone (AAR inducer), SB431542 (TGFβ inhibitor), CHIR99021 (WNT agonist) and PD0325901 (MEK/ERK inhibitor) fully counteract L-Pro supplementation effects (Comes et al, 2013;D'Aniello et al, 2015). Moreover, L-Pro impacts mTOR pathway in porcine trophectoderm cells (Liu et al, 2021).…”
Section: Proline Modulates Signaling Pathwayssupporting
confidence: 56%
“…As expected, specific signaling modulators such as halofuginone (AAR inducer), SB431542 (TGFβ inhibitor), CHIR99021 (WNT agonist) and PD0325901 (MEK/ERK inhibitor) fully counteract L-Pro supplementation effects (Comes et al, 2013;D'Aniello et al, 2015). Moreover, L-Pro impacts mTOR pathway in porcine trophectoderm cells (Liu et al, 2021).…”
Section: Proline Modulates Signaling Pathwayssupporting
confidence: 56%
“…Since SLC36A2 was found highly enriched in uEVs of pregnant mares and showed higher expression in the endometrium compared to the embryo, SLC36A2 mRNA and protein are probably secreted by the endometrium and transferred to the embryo. Previous in vitro studies with porcine trophoblast cells and mouse embryos 71 , 72 revealed an important role in providing proline which is essential for early embryonic development due to its role in the synthesis of polyamines 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, TAC represents the overall antioxidative activity of the organism and is also linked to lipid peroxidation to some extent (Li et al, 2019;Moradi, Goodarzi, et al, 2021). Consistently, recent investigations indicated that the supplementation of Proline enhances the activity of specific intracellular enzymatic and non-enzymatic antioxidants (Liu et al, 2021;Ponrasu et al, 2013).…”
Section: Discussionmentioning
confidence: 81%